Estudo do efeito da temperatura em sistema de eletrocoagulação para o tratamento de efluente têxtil - Silva, Luiz Thiago Vasconcelos da (2023)
The textile sector consumes large amounts of water in its process, generating a high volume of effluents containing various components (dyes, detergents, and dispersants). In this sense, among the methods of textile effluent treatment, the electrolytic processes present themselves as a very effective and versatile alternative method. Several factors already studied, such as type of current and electrode material, have proven to interfere with the effectiveness of the Electrocoagulation (EC) process. However, there are few studies reported in the literature on the study of the effect of temperature on the EC process. Thus, this work aims to study the effect of temperature on the CE process in the removal of the dye Remazol Red RB 133% from aqueous medium, in addition to studying the current efficiency and presence of surfactant Cetyltrimethylammonium bromide (CTABr), which can interfere with this process. Firstly, the validation of the analytical method of spectrophotometry in the ultraviolet and visible region was done for the quantification of the dye. After that, the study of the influence of the factors temperature, surfactant concentration and current in the removal of the Total Organic Carbon (TOC), and of the dye and in the current efficiency and the kinetic and thermodynamic study in different temperatures (25, 35, 45, 55 and 65 ºC) of the process of the removal of the dye were applied. The experiments were carried out in an electrochemical system with a cylindrical acrylic reactor with A304 stainless steel electrodes with pulsed direct current. The results showed that it was possible to validate the analytical method for quantification of the dye, which was affected by the matrix effect, the analytical curve showed a linear behavior with a coefficient of determination (R2) of 0.9999 and the quantification limit (QL) and detection limit (DL) of the dye were found to be 0.39 and 0.13 mg L-1, respectively. In the influence of the variables, the temperature favored the removal of the dye, but not the removal of TOC. The electrical current favored the removal of the dye and the TOC, the surfactant concentration had an inverse behavior, favoring the removal of TOC only. The response of current efficiency was positively influenced by the current and temperature, i.e., the increase of these variables causes an increase in efficiency, but the surfactant concentration had a negative effect on this response causing an inverse behavior. The kinetic study indicated the removal mechanism of Remazol Red RB 133% (RRRB133%) dye as a first order process (n = 1) and influenced by oxidative and adsorption processes, obtaining velocity constants of kobs = 1.337 e-14736/RT and k1 = 1.379 e-15173/RT, respectively. The thermodynamic data of ∆H≠, ∆G≠ and ∆S≠ found described the process as being endothermic, non-spontaneous and with a tendency to increase the organization of the medium, respectively, moreover the values and signs of these parameters when compared to literature data, prove the assumption of the kinetic study of a process with two coexisting mechanisms of electro-oxidation and electrocoagulation for removal of the dye RRRB133%.